GHS-R1a Deficiency Alleviates Depression-Related Behaviors After Chronic Social Defeat Stress - Guo, Li; Niu, Minglu; Yang, Jie; Li, Li; Liu, Shuhan; Sun, Yuxiang; Zhou, Zhishang; Zhou, Yu (Frontiers in Neuroscience, 2019)
Ghrelin is an important orexigenic hormone that regulates feeding, metabolism and glucose homeostasis in human and rodents. Ghrelin functions by binding to its receptor, the growth hormone secretagogue receptor 1a (GHS-R1a), which is widely expressed inside and outside of the brain. Recent studies suggested that acyl-ghrelin, the active form of ghrelin, is a persistent biomarker for chronic stress exposure. However, how ghrelin/GHS-R1a signaling contributes to stress responses and mood regulation remains uncertain. In this study, we applied the chronic social defeat stress (CSDS) paradigm to both GHS-R1a knock-out (Ghsr-/-) mice and littermate control (Ghsr+/+) mice, and then measured their depression- and anxiety-related behaviors. We found that Ghsr+/+ mice, but not Ghsr-/- mice, displayed apparent anxiety and depression after CSDS, while two groups mice showed identical behaviors at baseline, non-stress state. By screening the central and peripheral responses of Ghsr-/- mice and Ghsr+/+ mice to chronic stress, we found similar elevations of total ghrelin and adrenocorticotropic hormone (ACTH) in the serum of Ghsr-/- mice and Ghsr+/+ mice after CSDS, but decreased interleukin-6 (IL-6) in the serum of defeated Ghsr-/- mice compared to defeated Ghsr+/+ mice. We also found increased concentration of brain derived neurotropic factor (BDNF) in the hippocampus of Ghsr-/- mice compared to Ghsr+/+ mice after CSDS. The basal levels of ghrelin, ACTH, IL-6 and BDNF were not different between Ghsr-/- mice and Ghsr+/+ mice. Our findings thus suggested that the differential expressions of BDNF and IL-6 after CSDS may contribute to less anxiety and less despair observed in GHS-R1a-deficient mice than in WT control mice. Therefore, ghrelin/GHS-R1a signaling may play a pro-anxiety and pro-depression effect in response to chronic stress, while GHS-R1a deficiency may provide resistance to depressive symptoms of CSDS.